The evaluation of a company’s strategy by the ansoff’s product market matrix/Įmonės strategijos vertinimas pagal i. Ansoffo produkto-rinkos modelį - Ginevičius, Romualdas; Auškalnytė, Renata (Journal of Civil Engineering and Management, 2001)
The I. Ansoff’s theories take a considerable place in the evolution of the strategy research. In our opinion, his works are very important, because there is a clear boundary between the strategy formulation process and the strategy as the result of this process. On the grounds of Ansoff’s point of view and his product market matrix, we suggest a methodology for determining the strategy applied by the company. I. Ansoff suggested four types of strategy: penetration, product development, market development and diversification (Fig 1). The diversification strategy is the most risky and distracts the company from its production and marketing. Therefore, the penetration, product development and market development will be evaluated. For the first stage of research the evaluation criteria of expansion strategies are chosen. There is not any common criterion of strategy. For evaluating the market penetration strategy the following criteria are chosen: costs of work, costs of resources, productivity of works, promotion costs on the native market. For evaluating the product development strategy the following criteria are used: number of new products, expenses of R&D, number of people who work in R&D, number of sold licences and number of bought licences. For market development strategy evaluating the following criteria are applied: number of new geographical markets, promotion costs on new geographical markets, number of people who work in the new markets. These criteria help to gather data for further research. Then the dynamics of criteria changes is calculated according to the formula: where I p is the meaning of criterion at the beginning of the analyzed period, I pa is the meaning of criterion at its end. This formula helps to calculate the generalized index of expansion strategies according to the formula In the second stage, the priorities of the groups of a company’s products are calculated and a group of the product influencing the company’s strategy is chosen. On the grounds of sale and export indexes, the product group is attributed to the product life cycle phase. The company’s ability to apply strategy is calculated in the third stage of research. Therefore, we have chosen the coefficient K 0 describing the work of each unit, equipment, technology, employees and changes on the market. The coefficient is calculated by the formula Where T is is the time of product innovation, T r is the time of production and realization. The life cycle of product helps to calculate the coefficient K 0. Therefore, the time parameters of this cycle stages are chosen and calculated by regression analysis. Then the stochastic model of product life cycle is created (Fig 2). By a formula the coefficient is calculated and compared with K 0 of the most successful company on the market. Besides, the coefficient K 0 helps to calculate the boundaries of expansion strategy according to the formulas: In this article we have introduced a methodology of the strategy applied by the company. The methodology proves the fact that there is a connection between the strategy of a company and product life cycle. In addition, this methodology helps to plan the activity of a company in future. Article in Lithuanian. First Published Online: 30 Jul 2012